2022
DOI: 10.3390/cells11152402
|View full text |Cite
|
Sign up to set email alerts
|

The AGEs/RAGE Transduction Signaling Prompts IL-8/CXCR1/2-Mediated Interaction between Cancer-Associated Fibroblasts (CAFs) and Breast Cancer Cells

Abstract: Advanced glycation end products (AGEs) and the cognate receptor, named RAGE, are involved in metabolic disorders characterized by hyperglycemia, type 2 diabetes mellitus (T2DM) and obesity. Moreover, the AGEs/RAGE transduction pathway prompts a dysfunctional interaction between breast cancer cells and tumor stroma toward the acquisition of malignant features. However, the action of the AGEs/RAGE axis in the main players of the tumor microenvironment, named breast cancer-associated fibroblasts (CAFs), remains t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 126 publications
0
8
0
Order By: Relevance
“…The protein encoded by this gene is a cell-surface receptor found on phagocytic cells, such as macrophages and neutrophils, and is involved in the processes of phagocytosis and immune complex clearance [ 37 ]. CXCR1 is able to bind to the inflammatory cytokine IL-8 and trigger a cascade of events through intracellular G proteins that activate multiple signaling pathways [ 38 ]. Through bioinformatic analysis, researchers conducted an in-depth analysis of alveolar lavage fluid datasets for COVID-19 and asthma.…”
Section: Discussionmentioning
confidence: 99%
“…The protein encoded by this gene is a cell-surface receptor found on phagocytic cells, such as macrophages and neutrophils, and is involved in the processes of phagocytosis and immune complex clearance [ 37 ]. CXCR1 is able to bind to the inflammatory cytokine IL-8 and trigger a cascade of events through intracellular G proteins that activate multiple signaling pathways [ 38 ]. Through bioinformatic analysis, researchers conducted an in-depth analysis of alveolar lavage fluid datasets for COVID-19 and asthma.…”
Section: Discussionmentioning
confidence: 99%
“…It’s known that different immune cell subsets can be recruited into TME via interactions between chemokines and chemokine receptors, and affect tumor progression and therapeutic outcome [ 66 ]. Chemokines (CXCL12 [ 67 ], CXCL8 [ 68 ], CXCL5 [ 69 ]) and chemokine receptors (CXCR1/2 [ 70 ], CCR4 [ 71 , 72 ], CCR8 [ 73 ]) are well-known to deeply participate in the tumor development and progression in various cancers, including LUAD [ 74 ]. In the present study, we found that the expression of KIAA1199 was correlated with the levels of many chemokines (CXCL12, CXCL8, CXCL5) and chemokine receptors (CXCR1/2, CXCR4, CCR8) in LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…Santolla et al. ( 52 ) demonstrated that the paracrine signaling of IL-8/CXCR1/2 could effectively activate and induce the migration and invasion properties of MDA-MB-231 breast cancer cells. Similarly, Sun et al.…”
Section: The Role and Mechanism Of Cafs In Breast Cancermentioning
confidence: 99%